Breast brachytherapy - Strnad, Vratislav; Yashar, Catheryn (Brachytherapy, 2020)
Accelerated partial breast irradiation with brachytherapy is a treatment method with a very low risk profile. In fact, accelerated partial breast irradiation brachytherapy has been proven in randomized trials to have fewer late side effects than whole-breast irradiation. Notably, Grade 3 late side effects are extremely rare, and excellent to good cosmetic results are observed in well over 90% of patients. In this article, published side effects of breast brachytherapy are reviewed and appropriate management discussed.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Brachytherapy; Breast; Side effects